Juridical Review of Prisoners' Conditional Rights After Law No. 22 of 2022 on Corrections: Eliminating Discrimination for Special-Crime Inmates - Mahendra Setiadji; Syahrul Borman; M.Yustino Aribawa (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the implementation of prisoners’ conditional rights following the enactment of Law Number 22 of 2022 concerning Corrections, particularly regarding the elimination of discriminatory treatment in granting remission, assimilation, and parole for prisoners convicted of special crimes.Research Methodology: This research employs a normative juridical method using statutory, conceptual, and analytical approaches. Data were collected through a literature review of primary, secondary, and tertiary legal materials and analyzed qualitatively.Result: The findings indicate that Law Number 22 of 2022 strengthens the principle of non-discrimination by providing equal opportunities for all prisoners to obtain conditional rights based on objective criteria, including behavior, participation in correctional programs, and risk assessment results. The policy reflects a shift from a punitive approach toward rehabilitation and social reintegration. Nevertheless, implementation challenges remain, including differing public perceptions, institutional limitations, and the need for regulatory harmonization. Conclusions: The law represents a significant reform in Indonesia’s correctional system by promoting equality before the law, human rights protection, and rehabilitation-oriented corrections. The elimination of discriminatory requirements supports fairer treatment of prisoners and contributes to the effectiveness of correctional administration.Limitations: This study is limited to a normative legal analysis and does not comprehensively examine empirical implementation across correctional institutions.Contributions: The study contributes to the development of correctional law scholarship and provides policy recommendations for strengthening a fair, humane, and rightsbased correctional system.